Apicoplast biogenesis mediated by ATG8 requires the ATG12–ATG5-ATG16L and SNAP29 complexes in Toxoplasma gondii. Issue 4 (3rd April 2023) - Fu, Jiawen; Zhao, Lin; Pang, Yu; Chen, Heming; Yamamoto, Hayashi; Chen, Yuntong; Li, Zhaoran; Mizushima, Noboru; Jia, Honglin
ABSTRACT: In apicomplexan parasites, the macroautophagy/autophagy machinery is repurposed to maintain the plastid-like organelle apicoplast. Previously, we showed that in Toxoplasma and Plasmodium, ATG12 interacts with ATG5 in a non-covalent manner, in contrast to the covalent interaction in most organisms. However, it remained unknown whether apicomplexan parasites have functional orthologs of ATG16L1, a protein that is essential for the function of the covalent ATG12–ATG5 complex in vivo in other organisms. Furthermore, the mechanism used by the autophagy machinery to maintain the apicoplast is unclear. We report that the ATG12–ATG5-ATG16L complex exists in Toxoplasma gondii (Tg). This complex is localized on isolated structures at the periphery of the apicoplast dependent on TgATG16L. Inducible depletion of TgATG12, TgATG5, or TgATG16L caused loss of the apicoplast and affected parasite growth. We found that a putative soluble N-ethylmaleimide sensitive factor attachment protein receptor (SNARE) protein, synaptosomal-associated protein 29 (TgSNAP29, Qbc SNARE), is required to maintain the apicoplast in T. gondii . TgSNAP29 depletion disrupted TgATG8 localization at the apicoplast. Additionally, we identified a putative ubiquitin-interacting motif-docking site (UDS) of TgATG8. Mutation of the UDS site abolished TgATG8 localization on the apicoplast but not lipidation. These findings suggest that the TgATG12–TgATG5-TgATG16L complex is required for biogenesis of the apicoplast, in which TgATG8 is translocated to the apicoplast via vesicles in a SNARE -dependent manner in T. gondii . Abbreviations : AID: auxin-inducible degron; CCD: coiled-coil domain; HFF: human foreskin fibroblast; IAA: indole-3-acetic acid; LAP: LC3-associated phagocytosis; NAA: 1-naphthaleneacetic acid; PtdIns3P: phosphatidylinositol-3-phosphate; SNARE: soluble N-ethylmaleimide sensitive factor attachment protein receptor; UDS: ubiquitin-interacting motif-docking site; UIM: ubiquitin-interacting motif.